Anthropological Analysis of Celtic graves from Brežice and Dobova (Slovenia) - Hincak, Zdravka (Array, 2011)
Cremated human and animal osteological remains from Iron Age on archaeological sites Sejmišče in Brežice and Kosovka near Dobova (Slovenia) were analysed. Beside the content of urns and burned human and animals remains, unburned animal fragments as grave goods for both sides sites were also included in this study. The preservation of osteological and dental remains of human and animal origin was moderate. Apart from traditional macroscopic methods of analysing cremated remains, microscopic method for determination of sex and age at death were also tested. Fragments of humeral and femoral bone diaphysis of adult persons whose remains had been found on the sites were analysed microscopically. Person’s age at death was presented in the range of five or ten years, and the long bone fragments of a child (infants) were detected. Taxonomic position for each analysed specimen was determined by macroscopic and microscopic analysis of the cremated animal bones. The aim of analysis was to compare both sites anthropologically and zooarchaeologically and to determine similarities and differences between them. The results of analyses confirm validity of microscopic method in determination of sex and age at death for human remains and taxonomic qualification of cremated animal remains from archaeological sites.